Mystery Road. Series 2 [videorecording (DVD)] - Pedersen, Aaron, 1970-; Helin, Sofia, 1972-; Alberts, Jada; Mulvey, Callan, 1975- (Acorn Media, 2021)
Aaron Pedersen returns as Det. Jay Swan in this mystery set in the Australian outback. When a body is found along the coast, Jay teams up with a local constable to investigate. Facing obstruction from an archaeologist working nearby, Jay must expose the web of corruption plaguing the town as the body count rises.